A high-power solid state amplifier for Galileo satellite system exploiting European GaN technology. Issue 4 (8th March 2016) - Giofré, Rocco; Colantonio, Paolo; Cipriani, Elisa; Giannini, Franco; Gonzalez, Laura; De Arriba, Francisco; Cabria, Lorena
Abstract : This paper describes the development of an L-Band (f0 = 1.575 GHz) high power and efficient solid state power amplifier (SSPA) designed for the European satellite navigation system (i.e. Galileo). The amplifier, developed in the framework of the European Project named SLOGAN, exploits the GH50-10 GaN technology available at United Monolithic Semiconductor foundry. The aim of the project is to offer, using as much as possible European technologies, a valid alternative to replace traveling wave tube amplifiers with more compact and reliable systems. All the SSPA functionalities, i.e. power supply, power conditioning and radio frequency amplification, are integrated in the developed architecture and accommodated in a single box with limited volume and mass. The required output power level is achieved by parallelizing several GaN die power bars of 12 and/or 25.6 mm. In continuous wave operating mode, the overall SSPA delivers an output power higher than 250 W at less than 2 dB of gain compression in the whole E1-band. Moreover, the registered gain and efficiency are higher than 67 dB and 54%, respectively.